(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the research of the participation of the custom system in the foreign trade in the Azov-Black Sea region. The primary sources concerning the history of the custom line and their informative potentials for study some particularities of the foreign trade in the South of Ukraine (Azov-Black Sea region) are analysed (statistical data, descriptions of the prospects of the development of the foreign trade, problem of the illicit trade, use the foreign trade as a factor of the foreign and international policy).